2014
DOI: 10.1016/j.chom.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Recruited by IL-22 in Peripheral Tissues Function as TRAIL-Dependent Antiviral Effectors against MCMV

Abstract: SummaryDuring primary infection, murine cytomegalovirus (MCMV) spreads systemically, resulting in virus replication and pathology in multiple organs. This disseminated infection is ultimately controlled, but the underlying immune defense mechanisms are unclear. Investigating the role of the cytokine IL-22 in MCMV infection, we discovered an unanticipated function for neutrophils as potent antiviral effector cells that restrict viral replication and associated pathogenesis in peripheral organs. NK-, NKT-, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 58 publications
(52 reference statements)
1
67
0
Order By: Relevance
“…Airway neutrophilia is observed in patients with bronchiolitis (42), and an increase in neutrophils is detected in blood prior to the influx of CD8 T cells (43). We have previously observed persistent airway neutrophilia following regulatory T cell depletion (44), suggesting they are associated with disease, but other studies have demonstrated that neutrophils can have a protective (45) or antiviral (46) role. While RSV RNA and protein have been observed in airway neutrophils from infected infants (47), the data generated using GFP-expressing virus suggest that macrophages, but not neutrophils, can support viral replication.…”
Section: Discussionmentioning
confidence: 94%
“…Airway neutrophilia is observed in patients with bronchiolitis (42), and an increase in neutrophils is detected in blood prior to the influx of CD8 T cells (43). We have previously observed persistent airway neutrophilia following regulatory T cell depletion (44), suggesting they are associated with disease, but other studies have demonstrated that neutrophils can have a protective (45) or antiviral (46) role. While RSV RNA and protein have been observed in airway neutrophils from infected infants (47), the data generated using GFP-expressing virus suggest that macrophages, but not neutrophils, can support viral replication.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, it has been shown that IL-22 promotes accumulation of neutrophils in peripheral tissues, notably in the liver and lung, via CXCL1 production, the main neutrophil chemoattractant. 36 In fact, the role of neutrophils recruited in intestinal tissues of GVHD recipients contributes to tissue damage and aggravation of intestinal GVHD. 37 Whether donor-derived IL-22 and host type I IFN also participates in neutrophil recruitment during GVHD remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6 WT mice were purchased from Charles River or Envigo. Mice were infected with MCMV that was prepared by sorbital gradient purification as described previously [70]. Mice were infected with 3 × 10 4 pfu MCMV intraperitoneally (i.p.).…”
Section: Methodsmentioning
confidence: 99%